Serum-derived extracellular vesicles from breast cancer patients contribute to differential regulation of T-cell-mediated immune-escape mechanisms in breast cancer subtypes - Graham, Rosalind; Gazinska, Patrycja; Zhang, Birong; Khiabany, Atousa; Sinha, Shubhankar; Alaguthurai, Thanussuyah; Flores-Borja, Fabian; Vicencio, Jose; Beuron, Fabienne; Roxanis, Ioannis; Matkowski, Rafal; Liam-Or, Revadee; et al. (Frontiers in Immunology, 2023)
Breast cancer exhibits considerable molecular heterogeneity and the way in which the immune microenvironment responds to this heterogeneity remains unclear. Here, we examine the differential effects of breast cancer subtype-specific patient serum derived extracellular vesicles in the regulation of T cell mediated immune responses. Patients with triple negative breast cancers (TNBCs) exhibited the lowest number of extracellular vesicles in the sera; whilst the highest was detected in ER+HER2+ cancers; reflected also in the higher level of CD63+ vesicles found within the ER+HER2+ local tumour microenvironment. Transcriptomic analysis of the TCGA data identified that samples assigned with lower EV scores had significantly higher abundance of CD4+ memory activated T cells, T follicular cells and CD8 T cells, plasma, and memory B cells; whilst samples with high EV scores were more enriched for anti-inflammatory M2 macrophages and mast cells. A negative correlation between EV expression scores and stromal tumour infiltrating lymphocyte counts was also observed. In vitro experiments confirmed that circulating EVs within breast cancer subtypes have functionally differing immunomodulatory capabilities, with EVs from patients with the most aggressive breast cancer subtype (TNBCs) demonstrating the most immune-suppressive phenotype (decreased CD3+HLA-DR+ but increased CD3+PD-L1 T cells, increased CD4+CD127-CD25hi T regulatory cells with associated increase in IL10 secretion). Further investigations into the mechanisms driving these subtype specific differences of EV in the context of their host immune microenvironment are warranted.